Glass material for reheat pressing, glass material subjected to reheat pressing, polished glass and methods for producing the same

By forming a modified layer on the surface of the reheated pressed glass, the formation and intrusion of the crystalline layer are suppressed, the problems of unevenness of the finished glass products and material losses are solved, and efficient molding and improvement of finished product quality are achieved.

CN112142320BActive Publication Date: 2025-03-21HOYA CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010588162.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-06-24
Publication Date
2025-03-21
Estimated Expiration
2040-06-24

AI Technical Summary

Technical Problem

When reheating the glass, the formation of the surface crystal layer causes hard crystallization ends or corners to invade the inside of the glass, causing problems of foreign matter mixing and unevenness of the finished product, and the removal of the crystal layer increases material loss and waste.

Method used

A glass containing Li, Na, K, Rb, Cs, and Fr components was used, and a modified layer was formed on the surface. A surface modified layer with a thickness of less than 1000 nm was formed by impregnating the alkali metal molten salt to prevent the formation of the crystalline layer.

Benefits of technology

It effectively prevents the formation and invasion of hard crystalline layers, reduces the amount of grinding and polishing, and improves the homogeneity and yield of finished glass products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112142320B_ABST
    Figure CN112142320B_ABST
Patent Text Reader

Abstract

The present invention provides a glass material for reheat pressing in which a crystal layer on the surface of the glass material does not invade the interior of the glass material during reheat pressing, and a method for manufacturing the same. The glass material for reheat pressing of the present invention comprises glass and a surface modification layer covering the glass, wherein the glass contains Li, Na, K, Rb, Cs and Fr components, and the total content of these components is 1.2% by mass or less, and the content of at least one of the Li, Na, K, Rb, Cs or Fr components in the surface modification layer is greater than the content of the component in the glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a glass material for reheat pressing in which the glass surface is treated, a glass material subjected to reheat pressing, polished glass, and methods for producing the same. Background Art

[0002] As a molding method for optical glass, the following reheat pressing method is widely known: a glass material of a given shape (glass material for reheat pressing) is supplied to a mold having a lower mold and an upper mold, the glass material is heated and softened, and then pressed and molded by the above mold, and the molded glass is taken out. In addition, large-diameter optical lenses are difficult to manufacture by other methods, and the reheat pressing method is usually used.

[0003] However, if the glass material is placed in a mold of the reheat pressing method and heated, a hard layer caused by glass crystallization may be formed on the surface, making it difficult to soften. If the glass material is pressed in such a state, if the glass material has an angular shape, the hard crystal ends and corners may invade the interior of the lens material and cannot be removed by subsequent polishing, etc. In the worst case, crystals are also precipitated inside the glass material, making it impossible to obtain a homogeneous glass material.

[0004] In addition, in the case of a composition in which the material of the optical glass is easy to crystallize, the crystal layer formed on the surface of the glass material when heated and softened is thicker. In order to make the final product, a large amount of the crystal layer needs to be removed, so the material loss increases and the waste becomes more. In addition, glass has a smaller thermal conductivity than general mold materials, so even if it is the same glass material, in the reheat pressing process, when the temperature distribution in the glass material becomes larger and the degree of crystallization of the glass is different (for example, in the case of increasing the processing size to increase the diameter of the lens, in the case of wanting to improve the processing accuracy of the glass, and in the case of processing a shape with a thickness distribution, etc.), sometimes even if you want to suppress the crystallization of a specific part in the glass, you cannot suppress the crystallization of other parts, or you cannot get the target shape, and the problem of crystallization as mentioned above becomes more serious.

[0005] As such, glass molding by the reheat pressing method has various problems, and its difficulty has further increased in recent years. As a technology related to such a reheat pressing method, for example, Patent Document 1 discloses a technology for applying a coating film for demolding to a glass raw material. In addition, Patent Document 2 discloses a technology for using a glass molding mold containing carbon atoms without requiring a protective film on the mold surface.

[0006] However, these documents do not study a technique for preventing the end of the crystal layer of the optical glass material for reheat pressing from intruding into the interior.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 9-227136

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 2002-356334 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The present invention provides a glass material for reheat pressing, which can prevent foreign matter from being mixed into the glass material due to a part of the surface crystal layer at the end, corner, etc. intruding into the interior of the glass material when the glass material is heated and softened and pressed, thereby reducing the amount of grinding and polishing.

[0013] Solutions to the problem

[0014] The present inventors have studied a method for suppressing the formation of a surface crystal layer of glass and facilitating softening of glass by modifying the glass surface of glass having a total content of Li, Na, K, Rb, Cs and Fr of 1.2 mass % or less and / or lanthanum borate glass, thereby completing the present invention. The present invention includes the following contents.

[0015] [1] A glass material for reheat pressing, comprising glass and a surface modified layer covering the glass,

[0016] The glass contains a Li component, a Na component, a K component, a Rb component, a Cs component, and a Fr component, and the total content of these components is 1.2 mass % or less.

[0017] The surface modification layer contains at least one of the Li component, the Na component, the K component, the Rb component, the Cs component, and the Fr component in a larger amount than the glass.

[0018] [2] A glass material for reheat pressing, comprising lanthanum borate glass and a surface modification layer covering the glass,

[0019] The surface modification layer contains at least one of the Li component, the Na component, the K component, the Rb component, the Cs component, and the Fr component in a larger amount than the glass.

[0020] [3] The glass material for reheat pressing according to [1] or [2], wherein

[0021] The thickness of the surface modification layer is 1000 nm or less.

[0022] [4] The glass material for reheat pressing according to any one of [1] to [3] above, wherein

[0023] The content of each of Li, Na, K, Rb, Cs, and Fr components in the glass is 0.1 mass % or less.

[0024] [5] A glass material that has been subjected to reheat pressing, which is derived from the glass material for reheat pressing according to any one of [1] to [4] above.

[0025] [6] A polished glass obtained from the reheat-pressed glass material described in [5] above.

[0026] [7] A method for manufacturing a glass material for reheat pressing, the method comprising:

[0027] A process for manufacturing glass, comprising melting glass raw materials and then cooling the melt to obtain glass having a total content of Li, Na, K, Rb, Cs and Fr of 1.2 mass % or less; and

[0028] A step of immersing the glass in a molten salt containing at least one of Li, Na, K, Rb, Cs and Fr components to form a surface modification layer on the surface of the glass.

[0029] [8] A method for manufacturing a glass material for reheat pressing, the method comprising:

[0030] A process of melting a raw material of lanthanum borate series glass and then cooling it to produce lanthanum borate series glass;

[0031] A step of immersing the lanthanum borate-based glass in a molten salt containing at least one of Li, Na, K, Rb, Cs and Fr components to form a surface modification layer on the surface of the glass.

[0032] [9] A method for manufacturing a glass material that has been subjected to reheat pressing, the method comprising:

[0033] A step of reheat pressing the glass material for reheat pressing obtained by the production method according to [7] or [8] above.

[0034]

[10] A method for manufacturing polished glass, the method comprising:

[0035] A step of grinding and polishing the glass material obtained by the manufacturing method of [9] and subjected to reheat pressing.

[0036] Effects of the Invention

[0037] Even if the glass material for reheat pressing of the present invention is heated and softened, the formation of a hard surface crystal layer can be suppressed, and part of the surface crystal layer at the ends and corners can be prevented from invading the interior of the glass material during pressing, thereby reducing the amount of grinding and polishing. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a schematic diagram of reheat pressing without a surface modification layer.

[0039] Figure 2 is a schematic diagram of reheat pressing in the case of having a surface modification layer.

[0040] Figure 3 The following are photographs showing the production conditions of glass materials 1 to 4 for reheat pressing and a comparative glass material for reheat pressing, and their appearances after being heated for a predetermined time.

[0041] Figure 4 The following are photographs showing the production conditions of glass materials 5 to 8 for reheat pressing and a comparative glass material for reheat pressing, and their appearances after being heated for a predetermined time.

[0042] Figure 5 The following are photographs showing the production conditions of glass materials 9 to 12 for reheat pressing and a comparative glass material for reheat pressing, and their appearances after being heated for a predetermined time.

[0043] Figure 6 The following are photographs showing the production conditions of the glass materials 13 to 15 for reheat pressing and the comparative glass material for reheat pressing, and the appearances thereof when heated for a predetermined time.

[0044] Figure 7 The following are photographs showing the production conditions of the glass materials 16 to 17 for reheat pressing and the comparative glass material for reheat pressing, and the appearances thereof when heated for a predetermined time.

[0045] Figure 8 These are the results of measuring the glass material 7 for reheat pressing using LIBS (Laser Induced Breakdown Spectroscopy).

[0046] Explanation of symbols

[0047] 11.21 Glass

[0048] 11a, 21a Crystalline layer

[0049] 11b Intrusion into the crystal layer

[0050] 12, 22 upper mold

[0051] 13, 23 lower die DETAILED DESCRIPTION

[0052] [Glass materials for reheat pressing]

[0053] The following is a description of the glass material for reheat pressing. It should be noted that, in this specification, unless otherwise specified, the "%" used to indicate the glass composition means "mass %". In addition, in this specification, the "~" used to specify the numerical range means that both the upper limit and the lower limit are included in the range. For example, when the content of a glass constituent is expressed as "10-20%", it means more than 10 mass % and less than 20 mass %. In addition, the content of the glass constituent is set to the amount converted into oxides. In addition, the content (content) of the glass constituent can be quantified by known methods, such as inductively coupled plasma emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), etc. In the present invention, the content of a glass constituent of 0% means that the constituent is substantially not contained, and the constituent is allowed to be contained at an unavoidable impurity level.

[0054] In the present specification, the term “alkali metal” refers to Li (lithium), Na (sodium), K (potassium), Rb (rubidium), Cs (cesium), and Fr (francium).

[0055] In the present specification, the glass material for reheat pressing refers to a material for obtaining glass as a final product by using the material and passing through a reheat pressing step.

[0056] [Mother glass]

[0057] (First method)

[0058] The first mode of the glass material for reheat pressing of the present invention uses glass having a total content of alkali metal components (Li component (Li2O), Na component (Na2O), K component (K2O), Rb component (Rb2O), Cs component (Cs2O) and Fr component (Fr2O)) of 1.2 mass% or less (including 0 mass%) as mother glass.

[0059] The type of glass of the first embodiment is not particularly limited as long as it contains 1.2 mass % or less of alkali metal components in terms of oxides.

[0060] The content of each alkali metal component in the mother glass of the first mode is less than 1.2% relative to the total amount of glass on a metal oxide basis, and can be preferably set to less than 1.1%, less than 0.8%, less than 0.5%, less than 0.3%, less than 0.1%, less than 0.08%, less than 0.05%, less than 0.03%, less than 0.01%, or the content of all alkali metal components can be set to 0%. When the content of alkali metal components is small, there is an advantage of easily increasing the refractive index. It should be noted that the present invention can also be applied to the case of glass that becomes unstable (does not become glass but forms crystals) if it contains alkali metals.

[0061] The other glass components of the mother glass of the first embodiment are as follows.

[0062] The mother glass of the first embodiment may contain one or more of SiO2, P2O5 and B2O3. These components are components constituting the skeleton of glass, components that improve the thermal stability of glass, and components that contribute to low refractive index and low dispersion. The contents of SiO2, P2O5 and B2O3 are not particularly limited and may be set to any content. The upper limits of SiO2, P2O5, and B2O3 components can be, for example, less than 99%, less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, and less than 5%, respectively, and the lower limits can be, for example, more than 0%, more than 5%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 60%, more than 70%, more than 80%, and more than 90%, respectively.

[0063] In addition, there is no special limitation on the total content of SiO2, P2O5, and B2O3 components (SiO2+P2O5+B2O3), and any value may be taken. The upper limit of SiO2+P2O5+B2O3 may be, for example, less than 99%, less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, or less than 5%, and the lower limit may be, for example, more than 0%, more than 5%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 60%, more than 70%, more than 80%, or more than 90%.

[0064] The glass forming the matrix of the first embodiment may contain at least one of Li, Na, K, Rb, Cs and Fr, and the total content of these components is 1.2% by mass or less (including 0% by mass) as described above. Li2O, Na2O and K2O are components that improve the melting property of the glass and sometimes improve the thermal stability of the glass. They are also components that lower the transition temperature of the glass.

[0065] Among alkali metals, Li2O and Na2O components have a higher refractive index than K2O, Rb2O and Cs2O components, and sometimes contribute to high dispersion. The upper limit of the total content of Li2O and Na2O components (Li2O + Na2O) can be preferably set to 1.2% or less, 1.1% or less, 0.8%, 0.5% or less, 0.3% or less, 0.1% or less, 0.08% or less, 0.05% or less, 0.03% or less, or 0.01% or less relative to the total amount of glass, and the content of all alkali metal components can also be set to 0%.

[0066] The K2O component has a higher refractive index than the Rb2O and Cs2O components and sometimes contributes to high dispersion. The upper limit of the total content of Li2O, Na2O and K2O (Li2O+Na2O+K2O) obtained by adding K2O to the total content of the above-mentioned Li2O and Na2O can be preferably set to 1.2% or less, 1.1% or less, 0.8%, 0.5% or less, 0.3% or less, 0.1% or less, 0.08% or less, 0.05% or less, 0.03% or less, or 0.01% or less relative to the total amount of glass, and the content of all alkali metal components can also be set to 0%.

[0067] MgO, CaO, SrO, BaO and ZnO are components that improve the melting property of glass and sometimes improve the thermal stability of glass. In addition, MgO, CaO, SrO, BaO and ZnO are components that lower the glass transition temperature and sometimes have a higher refractive index than Na2O, K2O and Cs2O. There is no particular limitation on the content of each of MgO, CaO, SrO, BaO and ZnO. The upper limit of the content of each of MgO, CaO, SrO, BaO and ZnO can be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7% or less, 5% or less, 3% or less, 1% or less, or 0.5% or less.

[0068] The lower limit of the content of each of the MgO, CaO, SrO, BaO and ZnO components can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 60%, more than 70%, more than 80%, or more than 90%.

[0069] There is no particular limitation on the total content of each of MgO, CaO, SrO, BaO and ZnO components (MgO+CaO+SrO+BaO+ZnO), and the upper limit of MgO+CaO+SrO+BaO+ZnO can be, for example, less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, less than 7%, less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0070] The lower limit of the total content of each of MgO, CaO, SrO, BaO and ZnO components (MgO+CaO+SrO+BaO+ZnO) can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 60%, more than 70%, more than 80%, or more than 90%.

[0071] La2O3, Gd2O3, Y2O3 and Yb2O3 are components with a higher refractive index than MgO, CaO, SrO and BaO, and are components that contribute to high refractive index and low dispersion. Sometimes, the thermal stability of glass is improved by introducing La2O3, Gd2O3, Y2O3 and Yb2O3. The content of each of La2O3, Gd2O3, Y2O3 and Yb2O3 is not particularly limited, and the upper limit of the content of each of La2O3, Gd2O3, Y2O3 and Yb2O3 can be, for example, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7% or less, 5% or less, 3% or less, 1% or less, or 0.5% or less.

[0072] The lower limit of the content of each of La2O3, Gd2O3, Y2O3 and Yb2O3 components can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 60%, more than 70%, or more than 80%.

[0073] There is no special limitation on the total content of La2O3, Gd2O3, Y2O3 and Yb2O3 components (La2O3+Gd2O3+Y2O3+Yb2O3), and the upper limit of La2O3+Gd2O3+Y2O3+Yb2O3 can be less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, less than 7%, less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0074] The lower limit of the total content of La2O3, Gd2O3, Y2O3 and Yb2O3 components (La2O3+Gd2O3+Y2O3+Yb2O3) can be above 0%, above 1%, above 3%, above 5%, above 7%, above 10%, above 15%, above 20%, above 25%, above 30%, above 35%, above 40%, above 45%, above 50%, above 60%, above 70%, above 80%, above 90%.

[0075] TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 are components that contribute to high refractive index and high dispersion, and their introduction may improve the thermal stability of glass. The content of each of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 is not particularly limited, and the upper limit of each of the content of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7% or less, 5% or less, 3% or less, 1% or less, or 0.5% or less.

[0076] The lower limits of the contents of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 components can be above 0%, above 1%, above 3%, above 5%, above 7%, above 10%, above 15%, above 20%, above 25%, above 30%, above 35%, above 40%, above 45%, above 50%, above 60%, above 70%, above 80%.

[0077] There is no special limitation on the total content of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 (TiO2+Nb2O5+Ta2O5+WO3+Bi2O3). The upper limit of TiO2+Nb2O5+Ta2O5+WO3+Bi2O3 can be, for example, less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, less than 7%, less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0078] The lower limit of the total content of each component TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 (TiO2+Nb2O5+Ta2O5+WO3+Bi2O3) can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 60%, more than 70%, or more than 80%.

[0079] ZrO2 and Al2O3 components are components that improve chemical durability, and sometimes they are introduced to improve the thermal stability of glass. The content of each of ZrO2 and Al2O3 components is not particularly limited, and the upper limit of each of the content of ZrO2 and Al2O3 can be, for example, 30% or less, 20% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7%, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, or 0.5% or less.

[0080] The lower limits of the contents of each of the ZrO2 and Al2O3 components can be, for example, above 0%, above 1%, above 3%, above 4%, above 5%, above 6%, above 7%, above 8%, above 9%, above 10%, above 11%, above 12%, above 13%, above 14%, above 15%, above 20%, or above 25%.

[0081] As required, at least one of As2O3, Sb2O3 and SnO2 can be added to the glass. As2O3, Sb2O3 and SnO2 have the effect of clarifying the glass when it is melted, and the effect of reducing the platinum-containing substances (platinum foreign matter) in the obtained glass. In addition, the oxidation / reduction state of the glass can sometimes be adjusted. The contents of Ab2O3, Sb2O3, and SnO2 are not particularly limited. The upper limits of the contents of Ab2O3, Sb2O3, and SnO2 can be less than 1%, less than 0.9%, less than 0.8%, less than 0.7%, less than 0.6%, less than 0.5%, less than 0.4%, less than 0.3%, less than 0.2%, less than 0.1%, less than 0.09%, less than 0.08%, less than 0.07%, less than 0.06%, less than 0.05%, less than 0.04%, less than 0.03%, less than 0.02%, less than 0.01%, less than 0.009%, less than 0.008%, less than 0.007%, less than 0.006%, less than 0.005%, less than 0.004%, less than 0.003%, less than 0.002%, and less than 0.001%. In addition, the lower limits of the contents of As2O3, Sb2O3 and SnO2 can be above 0%, above 0.001%, above 0.002%, above 0.003%, above 0.004%, above 0.005%, above 0.006%, above 0.007%, above 0.008%, above 0.009%, above 0.01%, above 0.02%, above 0.03%, above 0.04%, above 0.05%, above 0.06%, above 0.07%, above 0.08%, above 0.09%, above 0.1%, above 0.2%, above 0.3%, above 0.4%, above 0.5%, above 0.6%, above 0.7%, above 0.8%, above 0.9%.

[0082] In addition, when there is a problem that a radioactive substance is contained in a material depending on the application, it is preferable to suppress the content of the radioactive isotope to a certain amount or less, or to intentionally not contain it (however, mixing as impurities is not prevented).

[0083] (Second method)

[0084] In the second aspect of the glass material for reheat pressing of the present invention, the mother glass is lanthanum borate glass.

[0085] The type of mother glass in the second embodiment is not particularly limited as long as it is lanthanum borate glass. Lanthanum borate glass is generally a high refractive index, low dispersion glass in optical glass applications, and the present invention can be applied to such glass.

[0086] In this specification, lanthanum borate glass refers to glass containing a B component (B2O3) and a La component (La2O3) as glass components.

[0087] In the second embodiment, the content of B2O3 is not particularly limited, and as its lower limit, it can be set to 1.0% or more, 5.0% or more, 7.0% or more, 8.0% or more, 9.0% or more, or 10.0% or more. On the other hand, as the upper limit of the B2O3 component, it can be set to 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 20% or less. From the perspective of maintaining the thermal stability of the glass, it is preferred that the content of B2O3 expressed in mass % is greater than the content of SiO2, and the content of B2O3 is greater than the content of P2O5. Similarly, from the perspective of maintaining the thermal stability of the glass, it is preferred that the content of B2O3 expressed in mass % is greater than the total content of SiO2 and B2O3.

[0088] In the second embodiment, the content of La 2 O 3 is not particularly limited, but its lower limit may be 10% or more, 12% or more, 15% or more, 17% or more, or 20% or more.

[0089] The upper limit of La2O3 can be set to 90% or less, 80% or less, 75% or less, 70% or less, 68% or less, 65% or less, 63% or less, or 60% or less.

[0090] In the second mode, SiO2 and P2O5 components are arbitrary components constituting the skeleton of glass, are components that improve the thermal stability of glass, and are components that contribute to low refractive index and low dispersion. The content of SiO2 and P2O5 components is not particularly limited and can be set to any content. The upper limits of SiO2 and P2O5 components can be, for example, less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, less than 5%, and the lower limits can be, for example, more than 0%, more than 5%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, respectively.

[0091] The lanthanum borate glass in the second embodiment may contain at least one of Li2O, Na2O, K2O, Rb2O and Cs2O. Among them, Li2O, Na2O and K2O are components that improve the meltability of glass, sometimes improve the thermal stability of glass, and are components that lower the transition temperature of glass. The contents of Li2O, Na2O, K2O, Rb2O and Cs2O components are not particularly limited when they are included in the mother glass, and can be set to any content. The upper limits of the contents of Li2O, Na2O, K2O, Rb2O and Cs2O components are, for example, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7.5% or less, 5.0% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, 1.0% or less, or 0.5% or less, and the lower limits are, for example, 0% or more, 0.1% or more, 0.2% or less, 0.3% or less, 0.4% or less, 0.6% or less, 0.7% or less, 0.8% or less, 0.9% or less, 0.1% or less, 0.2% or less, 0.3% or less, 0.4% or less, 0.5% or less, 0.6% or less, 0.7% or less, 0.8% or less, 0.9% or less, 0.1% or less, 0. %, more than 0.5%, more than 1.0%, more than 1.5%, more than 2.0%, more than 2.5%, more than 3.0%, more than 3.5%, more than 4.0%, more than 5.0%, more than 7.5%, more than 10.0%, more than 15.0%, more than 20.0%, more than 25.0%, more than 30.0%, more than 35.0%, more than 40.0%, more than 45.0%, and may not contain any of Li2O, Na2O, K2O, Rb2O and Cs2O components.

[0092] Among alkali metals, Li2O and Na2O components have a higher refractive index than K2O, Rb2O, and Cs2O components, and sometimes contribute to high dispersion. The total content of Li2O and Na2O components (Li2O+Na2O) may be, for example, 0.1% or less, 0.5% or less, 1.0% or less, 1.5% or less, 2.0% or less, 2.5% or less, 3.0% or less, 3.5% or less, 4.0% or less, 5.0% or less, 7.5% or less, 10.0% or less, 15.0% or less, 20.0% or less, 25.0% or less, 30.0% or less, 35.0% or less, 40.0% or less, 45.0% or less, or 50.0% or less when these components are contained.

[0093] The lower limit of the total content of Li2O and Na2O components (Li2O + Na2O) can be, for example, more than 0%, more than 0.1%, more than 0.5%, more than 1.0%, more than 1.5%, more than 2.0%, more than 2.5%, more than 3.0%, more than 3.5%, more than 4.0%, more than 5.0%, more than 7.5%, more than 10.0%, more than 15.0%, more than 20.0%, more than 25.0%, more than 30.0%, more than 35.0%, more than 40.0%, or more than 45.0%.

[0094] The K2O component has a higher refractive index than the Rb2O and Cs2O components and sometimes contributes to high dispersion. The total content of Li2O, Na2O and K2O (Li2O+Na2O+K2O) obtained by adding K2O to the total content of the above-mentioned Li2O and Na2O is not particularly limited, and its upper limit may be, for example, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7.5% or less, 5.0% or less, 4.0% or less, 3.5% or less, 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, 1.0% or less, or 0.5% or less.

[0095] The lower limit of the total amount of Li2O, Na2O and K2O components (Li2O+Na2O+K2O) can be, for example, more than 0%, more than 0.1%, more than 0.5%, more than 1.0%, more than 1.5%, more than 2.0%, more than 2.5%, more than 3.0%, more than 3.5%, more than 4.0%, more than 5.0%, more than 7.5%, more than 10.0%, more than 15.0%, more than 20.0%, more than 25.0%, more than 30.0%, more than 35.0%, more than 40.0%, or more than 45.0%.

[0096] MgO, CaO, SrO, BaO and ZnO are components that improve the melting property of glass and sometimes improve the thermal stability of glass. In addition, MgO, CaO, SrO, BaO and ZnO are components that lower the glass transition temperature and sometimes have a higher refractive index than Na2O, K2O and Cs2O. There is no particular limitation on the content of each of MgO, CaO, SrO, BaO and ZnO. The upper limit of the content of each of MgO, CaO, SrO, BaO and ZnO can be 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7% or less, 5% or less, 3% or less, 1% or less, or 0.5% or less.

[0097] The lower limit of the content of each of MgO, CaO, SrO, BaO and ZnO components can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, or more than 45%.

[0098] There is no particular limitation on the total content of each of MgO, CaO, SrO, BaO and ZnO components (MgO+CaO+SrO+BaO+ZnO), and the upper limit of MgO+CaO+SrO+BaO+ZnO may be, for example, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, less than 7%, less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0099] The lower limit of the total content of each of MgO, CaO, SrO, BaO and ZnO components (MgO+CaO+SrO+BaO+ZnO) can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, or more than 45%.

[0100] Gd2O3, Y2O3 and Yb2O3 are components with a higher refractive index than MgO, CaO, SrO and BaO, and are components that contribute to high refractive index and low dispersion. The thermal stability of glass may be improved by introducing Gd2O3, Y2O3 and Yb2O3. The content of each of La2O3, Gd2O3, Y2O3 and Yb2O3 is not particularly limited, and the upper limit of the content of each of Gd2O3, Y2O3 and Yb2O3 can be, for example, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7% or less, 5% or less, 3% or less, 1% or less, or 0.5% or less.

[0101] The lower limit of the content of each of the Gd2O3, Y2O3 and Yb2O3 components can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, or more than 45%.

[0102] There is no special limitation on the total content of La2O3, Gd2O3, Y2O3 and Yb2O3 components (La2O3+Gd2O3+Y2O3+Yb2O3), and the upper limit of La2O3+Gd2O3+Y2O3+Yb2O3 can be less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, less than 7%, less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0103] The lower limit of the total content of La2O3, Gd2O3, Y2O3 and Yb2O3 components (La2O3+Gd2O3+Y2O3+Yb2O3) can be above 5%, above 7%, above 10%, above 15%, above 20%, above 25%, above 30%, above 35%, above 40%, or above 45%.

[0104] TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 are components that contribute to high refractive index and high dispersion, and their introduction may improve the thermal stability of glass. The content of each of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 is not particularly limited, and the upper limit of each of the content of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 7% or less, 5% or less, 3% or less, 1% or less, or 0.5% or less.

[0105] The lower limits of the contents of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 components can be above 0%, above 1%, above 3%, above 5%, above 7%, above 10%, above 15%, above 20%, above 25%, above 30%, above 35%, above 40%, above 45%, above 50%, above 60%, above 70%, above 80%.

[0106] There is no special limitation on the total content of TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 (TiO2+Nb2O5+Ta2O5+WO3+Bi2O3). The upper limit of TiO2+Nb2O5+Ta2O5+WO3+Bi2O3 can be, for example, less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, less than 10%, less than 7%, less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0107] The lower limit of the total content of each component TiO2, Nb2O5, Ta2O5, WO3 and Bi2O3 (TiO2+Nb2O5+Ta2O5+WO3+Bi2O3) can be, for example, more than 0%, more than 1%, more than 3%, more than 5%, more than 7%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 60%, more than 70%, or more than 80%.

[0108] ZrO2 and Al2O3 components are components that improve chemical durability, and sometimes the thermal stability of glass can be improved by introducing them. The content of each of the ZrO2 and Al2O3 components is not particularly limited, and the upper limit of each of the ZrO2 and Al2O3 contents can be, for example, 30% or less, 20% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7%, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, or 0.5% or less.

[0109] The lower limits of the contents of each of the ZrO2 and Al2O3 components can be, for example, above 0%, above 1%, above 3%, above 4%, above 5%, above 6%, above 7%, above 8%, above 9%, above 10%, above 11%, above 12%, above 13%, above 14%, above 15%, above 20%, or above 25%.

[0110] As required, at least one of As2O3, Sb2O3 and SnO2 can be added to the glass. As2O3, Sb2O3 and SnO2 have the effect of clarifying the glass when it is melted and reducing the platinum-containing substances in the obtained glass. In addition, the oxidation / reduction state of the glass can sometimes be adjusted. The contents of Ab2O3, Sb2O3, and SnO2 are not particularly limited. The upper limits of the contents of Ab2O3, Sb2O3, and SnO2 can be less than 1%, less than 0.9%, less than 0.8%, less than 0.7%, less than 0.6%, less than 0.5%, less than 0.4%, less than 0.3%, less than 0.2%, less than 0.1%, less than 0.09%, less than 0.08%, less than 0.07%, less than 0.06%, less than 0.05%, less than 0.04%, less than 0.03%, less than 0.02%, less than 0.01%, less than 0.009%, less than 0.008%, less than 0.007%, less than 0.006%, less than 0.005%, less than 0.004%, less than 0.003%, less than 0.002%, and less than 0.001%. In addition, the lower limits of the contents of As2O3, Sb2O3 and SnO2 can be above 0%, above 0.001%, above 0.002%, above 0.003%, above 0.004%, above 0.005%, above 0.006%, above 0.007%, above 0.008%, above 0.009%, above 0.01%, above 0.02%, above 0.03%, above 0.04%, above 0.05%, above 0.06%, above 0.07%, above 0.08%, above 0.09%, above 0.1%, above 0.2%, above 0.3%, above 0.4%, above 0.5%, above 0.6%, above 0.7%, above 0.8%, above 0.9%.

[0111] (Preferred method)

[0112] In the present invention, it is preferred to simultaneously satisfy the features of the first embodiment and the second embodiment, wherein the first embodiment is characterized in that the total content of the Li component, the Na component, the K component, the Rb component, the Cs component, and the Fr component of the mother glass is 1.2 mass % or less; and the second embodiment is characterized in that the mother glass is a lanthanum borate glass. That is, in the present invention, it is preferred to use a lanthanum borate glass in which the total content of the Li component, the Na component, the K component, the Rb component, the Cs component, and the Fr component is 1.2 mass % or less (including 0 mass %) as the mother glass.

[0113] In the case where the mother glass is a lanthanum borate glass in which the total content of Li, Na, K, Rb, Cs and Fr components is less than 1.2 mass%, the content of the alkali metal component in the glass components can be set to the content described in the first method, and the other glass components can be set to the content described in the second method.

[0114] [Glass properties]

[0115] The glass material for reheat pressing of the present invention is a material suitable for molding by pressing in a state softened by heating.

[0116] The shape of the glass material for reheat pressing is not particularly limited, and examples thereof include: polyhedrons such as cuboids and cubes, and cylinders. These shapes all have ends and corners. When the ends and corners of the glass material are crystallized, they become difficult to soften, and the shape of the ends or corners remains directly. However, by having a surface modification layer such as the present invention, the ends and corners are softened by heating instead of being directly solidified, and the glass material is round. By pressing in this state, the crystallized layer is not easy to enter the interior of the glass. It should be noted that as the glass material for reheat pressing, drips directly obtained from molten glass can also be used.

[0117] The glass that becomes the matrix of the glass material for reheat pressing is preferably an optical glass, and more preferably an optical glass for the purpose of lens molding. The refractive index nd of the glass is not particularly limited, and its lower limit may be 1.30 or more, or 1.40 or more, 1.50 or more, 1.60 or more, 1.70 or more, 1.80 or more, 1.90 or more, 2.00 or more, 2.10 or more, or 2.20 or more. The upper limit of the refractive index nd may be 2.70 or less, or 2.60 or less, 2.50 or less, 2.40 or less, 2.30 or less, 2.20 or less, 2.10 or less, 2.00 or less, 1.90 or less, 1.80 or less, 1.70 or less, 1.60 or less, 1.50 or less, or 1.40 or less. The Abbe number νd is not particularly limited, and the lower limit thereof may be 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, 35 or more, 40 or more, 45 or more, 50 or more, 55 or more, 60 or more, 65 or more, 70 or more, 75 or more, 80 or more, 85 or more, 90 or more, 95 or more, or 100 or more. The upper limit of the Abbe number νd may be 150 or less, 140 or less, 130 or less, 120 or less, 110 or less, 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, 55 or less, 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, or 20 or less.

[0118] In addition, when there is a problem that a radioactive substance is contained in a material depending on the application, it is preferable to suppress the content of the radioactive isotope to a certain amount or less, or to intentionally not contain it (however, mixing as impurities is not prevented).

[0119] [Surface modification layer]

[0120] The surface modified layer is characterized in that the content of at least one of the Li component, Na component, K component, Rb component, Cs component and Fr component is higher than the content of the component in the glass as the matrix. The surface modified layer is also glass, so it is difficult to confirm the boundary with the glass as the matrix, but when the component amount is measured from the surface toward the center of the glass as the matrix for the reheat pressing of the present invention, there is a part near the surface where the content of at least one of the Li component, Na component, K component, Rb component, Cs component or Fr component is higher than the content of the Li component, Na component, K component, Rb component, Cs component or Fr component in the matrix glass, and this part is referred to as the surface modified layer in this specification.

[0121] The lower limit of the thickness of the surface modified layer is not particularly limited, but according to the results of component analysis, it is preferably 5000 nm or less, more preferably 3000 nm or less, further preferably 1000 nm or less, further preferably 500 nm or less, and particularly preferably 300 nm or less from the surface of the glass material for reheat pressing. When it is 5000 nm or less, the surface modified layer can be removed by grinding and polishing after pressing.

[0122] The lower limit of the thickness of the surface modification layer is not particularly limited, but is preferably 1 nm or more, and more preferably 10 nm or more. When it is 10 nm or more, the surface of the glass material for re-hot pressing has high stability and is easily softened by heating.

[0123] It should be noted that, for the thickness of the surface modification layer, the position where the intensity measured by LIBS (Laser Induced Breakdown Spectroscopy) of the portion containing more alkali metals in the surface modification layer reaches the same intensity as the maximum intensity of LIBS of the untreated glass is taken as the boundary. Figure 8 In the figure, the boundary of LIBS of glass treated with NaNO3 is the same as the maximum intensity of untreated glass at the position of 5 Shot, so the boundary between glass and surface modification layer can be 500nm.

[0124] [Reheat pressed glass material and polished glass]

[0125] The reheat pressed glass material of the present invention is suitable as a material for manufacturing polished glass, and is particularly suitable as a material for manufacturing glass optical elements, such as optical lenses. In order to manufacture polished glass using the reheat pressed glass material, the reheat pressed glass material is first reheat pressed to manufacture the reheat pressed glass material. Next, the reheat pressed glass material is ground and polished to manufacture polished glass. In the manufacture using the reheat pressed glass material of the present invention, since the crystal layer is not easily mixed into the glass due to reheat pressing, the product is of high quality and has a high yield rate, and the crystal layer formed by heating can be further thinned, thereby reducing the amount of glass to be removed by grinding and polishing.

[0126] [Method for producing glass material for reheat pressing]

[0127] (Immersion process)

[0128] The manufacturing method of the glass material for reheat pressing is described. The glass material for reheat pressing can be manufactured as follows: a glass material (mother glass) in a plate or rod shape or the like is cut into a given size (sometimes referred to as "slice" in this specification), or a drop obtained directly from molten glass is immersed in a molten salt of an alkali metal (a molten salt containing at least one of Li, Na, K, Rb, Cs and Fr).

[0129] As the molten salt containing at least one of Li component, Na component, K component, Rb component, Cs component and Fr component, as long as it is the molten salt containing at least one of Li component, Na component, K component, Rb component, Cs component and Fr component, it is not particularly limited, from the viewpoint of easy handling, lithium nitrate (LiNO3), sodium nitrate (NaNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), sodium carbonate (Na2CO3), potassium carbonate (K2CO3), rubidium carbonate (Rb2CO3), cesium carbonate (Cs2CO3) and a mixture of 2 or 3 kinds selected from their above-mentioned molten salts. The mixing ratio of the mixture can be arbitrarily determined. As a component, preferably Na component, if it is a mixture of Na component and K component, then more preferably Na component is more.

[0130] The temperature during immersion is not particularly limited as long as the molten salt containing at least one of the Na component, K component, Rb component, Cs component and Fr component is in a molten state. The lower limit temperature is above the melting point of each salt, preferably above 308°C, more preferably above 320°C, and the upper limit temperature is preferably below 800°C, more preferably below 600°C.

[0131] As for the immersion time, it is sufficient as long as the alkali component of the molten salt penetrates into the glass. If the immersion time is too long, there is a concern that the manufacturing efficiency will deteriorate. For example, the lower limit of the immersion time is preferably 10 minutes, more preferably 30 minutes, and the upper limit of the immersion time is preferably 24 hours or less, more preferably 12 hours or less, further preferably 6 hours or less, and further preferably 2 hours or less.

[0132] Regarding the formation of the surface modification layer by the above-mentioned impregnation process, it is believed that the alkali metal component from the molten salt only invades the surface layer of the glass to form a surface modification layer with relatively high stability. It should be noted that it can be considered that if the alkali metal salt invades, it is not easy to form a hard crystal layer even if it is heated to near the softening temperature of the glass. It should be noted that even if the glass is unstable when containing alkali metal components, it is sometimes possible to form a surface modification layer with relatively high stability by the impregnation process.

[0133] [Reheat pressing process, grinding and polishing process]

[0134] Next, the molding of glass will be described. The glass material for reheat pressing of the present invention is suitable for reheat pressing.

[0135] (Reheat Pressing Process)

[0136] Reheat pressing will be described using the drawings. Figure 1 This is a schematic diagram of reheat pressing of a material without a surface modification layer.

[0137] The glass 11 of a given shape is placed in the lower mold 13 of the press and heated to soften it ( Figure 1 (a)). At this time, if the heating temperature is too high, the glass becomes molten and liquefies in the mold and cannot be formed. If the heating temperature is too low, the glass material is in a hard state and cannot be formed. Therefore, the softening temperature is preferably in the range of 100°C lower than the softening point of the glass to be formed to 300°C higher than the softening point of the glass. The softening point of the glass refers to the value measured by the method specified in JIS R3103-1:2001.

[0138] However, at a temperature near the softening point, a hard surface crystal layer 11a is formed on the surface depending on the type of glass, and the corners of the surface crystal layer of the glass material remain ( Figure 1 (b)). In this state, when pressing is performed with the upper mold 12 and the lower mold 13, the hardened corners will invade the interior of the glass material ( Figure 1 (c) to (d)), even if grinding and polishing are performed after hot pressing, the corners that have intruded into the interior (the intruding crystal layer 11 (b)) cannot be removed ( Figure 1 (e)).

[0139] On the other hand, in the case of glass having a surface treatment layer (see Figure 2 , where the surface modified layer and the glass have no clear boundary and are not shown in the figure), the surface stability of the glass 21 is high, and the surface crystal layer 21a formed at a temperature near the softening point is different from the surface modified layer 21a without the surface treated layer. Figure 1 In addition, the reheat pressing glass material 21 having corners softens by heating, and the corners disappear ( Figure 2 (b)). In this state, even if the upper mold 22 and the lower mold 23 are pressed, no Figure 1 The intrusion crystal layer is free of foreign matter inside the molded glass. Figure 2 (c) to (d)). Therefore, the surface crystal layer 21a can be completely removed by grinding and polishing after reheat pressing ( Figure 2 (e) Reference).

[0140] (Grinding and polishing process)

[0141] After the reheat pressing, the reheat pressed glass material is ground and polished, thereby producing a polished glass as a final product. The obtained polished glass is suitable for use as an optical lens. The grinding and polishing can be carried out by the conventional method.

[0142] Grinding and polishing The glass that becomes the final product is obtained through various common grinding and polishing steps, but generally speaking, about 100 μm to 500 μm is ground and polished from the surface. If the reheat pressing glass material of the present invention is used, the thickness of the surface crystal layer is thin, and the crystal surface layer does not invade the interior, so the amount of grinding and polishing can be reduced.

[0143] It should be noted that existing materials can be used as the materials used for grinding and polishing.

[0144] Example

[0145] The present invention is further described below by way of examples. It should be noted that the present invention is not limited to the examples. It should be noted that in this example, a reheat pressing glass material is used to manufacture a reheat pressing optical glass lens material and mold an optical glass lens.

[0146] [Manufacturing of optical glass slices]

[0147] First, glass raw materials (content ratio in mass %, glass composition No. 1) were prepared so as to obtain glass having the following composition, melted at 1400° C., cast in a mold, and annealed at 730° C. to obtain a plate-shaped optical glass.

[0148]

[0149] The glass properties include Tg (glass transition temperature) of 709° C., nd (refractive index) of 2.001, and νd (Abbe number) of 29.13.

[0150] The obtained plate-like optical glass was cut into a rectangular parallelepiped shape of 10 mm (length)×10 mm (width)×9.0 mm (height), and a plurality of slices of the same shape were obtained.

[0151] [Manufacturing of optical glass lens materials for reheat pressing]

[0152] (Example 1)

[0153] The entire slice was immersed in 70 ml of 100 mol % NaNO 3 molten salt heated to 350° C. for 60 minutes to obtain an optical glass lens material 1 for reheat pressing.

[0154] (Examples 2 to 13)

[0155] The type of molten salt (NaNO3, or a 1:1 mixture of NaNO3 and KNO3), immersion temperature (Immersion temp. (°C)), and immersion time (Immersion time (min)) were changed to Figure 3 to Figure 7 Except for the above numerical values, the slices were dipped and sliced ​​in the same manner as in Example 1 to obtain optical glass lens materials 2 to 13 for reheat pressing.

[0156] [Thickness measurement after reheating test]

[0157] The reheat pressed optical glass lens materials 1 to 13 were kept at 700°C for 10 minutes in an annealing furnace, and then heated at 880°C for 10 minutes before being taken out. The heights of the reheat pressed optical glass lenses 1 to 13 after heating were measured, and the reduction (Δt) relative to the height before heating (9.0 mm) was calculated (described in Figure 3 to Figure 7 ). In addition, after heating, the entire surface of the reheat pressed optical glass lenses 1 to 13 turned white, and it was confirmed that they were covered with a surface crystal layer. In addition, the unimpregnated slices (comparative reheat pressed optical glass lens materials) were similarly subjected to the reheating experiment, and the thickness of the slices was measured. It was confirmed that the unimpregnated slices were also covered with a surface crystal layer. Photos of the reheat pressed optical glass lens materials 1 to 13 and the comparative reheat pressed optical glass lens materials after the reheating experiment are also shown. Figures 3 to 7 .

[0158] [Thickness of surface crystal layer]

[0159] The heated reheat pressed optical glass lens material 7 was cut, and the thickness of the surface crystal layer was measured by photographing, etc., and the result was 20μm. Similarly, the comparison reheat pressed optical glass lens was cut, and the thickness of the surface crystal layer was measured by photographing, etc., and the result was 50μm. The composition of the surface part including the surface modified layer is changed, and it is covered with a surface crystal layer that is not a hard crystal, and the slice becomes a state close to a spherical shape with the corners removed. If it is such a slice, the corner will not invade the glass during reheat pressing, and the thin surface crystal layer is of a thickness that can be fully removed by grinding and polishing the glass.

[0160] [Components of the surface modification layer]

[0161] The Na content of the surface modified layer of the reheat-pressed optical glass lens material (before reheat-pressing) can be measured by, for example, LIBS (Laser Induced Breakdown Spectroscopy, using an apparatus manufactured by Applied Spectra). LIBS was used in the following measurement.

[0162] The composition of the surface modified layer of the reheat pressed optical glass lens material 7 (before reheat pressed) was measured using such an apparatus. The results are shown in FIG. Figure 8 It is known that although the mother glass does not contain Na, there is a lot of Na at a given distance (about 500 nm) from the surface. It is presumed that this is because Na penetrates into the glass due to immersion.

[0163] As in the above example, glass composition No. 2 to 31 described in Table 1 was used instead of glass composition No. 1, and the temperature was changed to an appropriate temperature according to the characteristics of the glass. The same experiment as in Example 1 was conducted. As a result, in the slice immersed in the molten salt, the composition of the surface part including the surface crystal layer was changed, and the slice became a state close to a spherical shape with corners removed instead of hard crystals. If it is such a slice, the corners will not penetrate into the glass during reheat pressing, and the thin surface crystal layer is of a thickness that can be fully removed by grinding and polishing the glass.

[0164] For each slice, it was confirmed that: by immersing in alkali metal molten salt, the thickness of the surface crystal layer can be reduced; the composition of the surface portion including the surface crystal layer is changed, and the slice is not hard crystallized, but can be made into a state close to a spherical shape with corners removed. If it is such a slice, the corner can be suppressed from intruding into the glass during reheat pressing. In addition, the thin surface crystal layer of these examples is a thickness that can be fully removed by grinding and polishing the glass.

[0165] The various glass materials for reheat pressing thus prepared were heated, softened, and reheat pressed to produce lens blanks with shapes similar to optical lenses. The lens blanks were observed and it was confirmed that no end or corner of the glass material penetrated into the glass of the surface crystal layer.

[0166] The surface of the reheat pressed glass material after the reheat press molding was analyzed by the same method as the surface analysis of the reheat pressed glass material, thereby confirming the presence of a surface modified layer similar to that of the reheat pressed glass material.

[0167] Next, the lens blanks are ground and polished to produce various optical lenses. Since the ends and corners of the glass material in the lens blanks do not penetrate into the glass inside the surface crystal layer, the amount of grinding and polishing can be reduced.

[0168] It should be noted that the above-mentioned reheat press molding, grinding, and polishing can be performed by known methods.

[0169] The above describes the production of optical lenses. The present invention can be applied not only to optical lenses but also to the production of various optical elements made of glass such as prisms and the production of glass articles other than optical elements.

[0170]

[0171] Industrial Applicability

[0172] The present invention is useful in the technical field of optical glass. In particular, the glass of the present invention has the characteristic of reducing surface devitrification during reheating, and is therefore particularly suitable for the manufacture of glass including a reheating process, but can also be used for various purposes other than reheat pressing.

Claims

1. A glass material for reheat pressing, comprising: Lanthanum borate glasses, and a surface modification layer covering the glass, The glass contains at least one of a Li component, a Na component, a K component, a Rb component, and a Cs component, and the total content of these components is 1.2 mass % or less, The surface modification layer contains at least one of a Li component, a Na component, a K component, a Rb component, and a Cs component in a larger amount than the glass.

2. The glass material for reheat pressing according to claim 1, wherein: The thickness of the surface modification layer is less than 1000 nm.

3. The glass material for reheat pressing according to claim 1 or 2, wherein: The content of each of the Li component, the Na component, the K component, the Rb component, and the Cs component in the glass is 0.1 mass % or less. 4 . A reheat-pressed glass material, which is derived from the reheat-pressed glass material according to claim 1 .

5. A polished glass obtained from the reheat-pressed glass material according to claim 4.

6. The method for producing a glass material for reheat pressing according to any one of claims 1 to 3, comprising: A process for manufacturing lanthanum borate series glass by melting a raw material of lanthanum borate series glass and then cooling the raw material; as well as The step of immersing the lanthanum borate glass in a molten salt containing at least one of a Li component, a Na component, a K component, a Rb component, and a Cs component to form a surface modification layer on the surface of the glass.

7. A method for manufacturing a glass material that has been subjected to reheat pressing, the method comprising: A step of reheat pressing the glass material for reheat pressing obtained by the production method according to claim 6.

8. A method for manufacturing polished glass, the method comprising: A step of grinding and polishing the glass material obtained by the production method of claim 7 and subjected to reheat pressing.

Citation Information

Patent Citations

  • Mold for forming glass and method for manufacturing the mold

    JP2002356334A

  • Ophthalmic and optical glass

    US4732876A

  • Glass with high refractive index

    WO2016013612A1